MEMORIZATION STRATEGY DURING LEARNING PROCESS: STUDENTS' REVIEW - Ajeng Muliagita Kiswardhani; Mutiara Ayu (fsip.teknokrat.ac.id, 2021)
The purpose of this research is to determine about how the attitude of using the memorization strategy towards students' learning activities. This research using a quantitative methods. The sample of this research were 38 students from English Education in a private university. They consist of male and female sixth-semester students. The research instrument in the form of a questionnaire obtained through google form, then the data will be analyzed using SPSS to find out how students' attitudes towards the learning strategy of memorization. The results of this study indicate that the student's attitude towards the memorization learning strategy show a positive attittude, it can be seen from the results of the questionnaire that has been filled out by the participants. According to their responses, the memorization strategy also made it easier for them to absorb lesson information. These findings can be used by teachers or lecturers to apply the memorization strategy as an effective learning strategy for the students.